Polymer-coated cardiopulmonary bypass circuit attenuates upregulation of both proteases/protease inhibitors and platelet degranulation in pigs. (November 2017) - Suehiro, Shoichi; Shimizu, Kouji; Imai, Kensuke; Niii, Atsushi; Akeho, Kazuhiro; Nakata, Hayato; Yamaguchi, Akane; Matsumoto, Ken-ichi; Oda, Teiji
Introduction: Interaction of blood with a cardiopulmonary bypass (CPB) circuit activates the coagulation-fibrinolysis, complement and kinin-kallikrein systems that are mainly supported by proteases and their inhibitors. Methods: Biocompatibility of a new polymer-coated (SEC-coated) CPB circuit was globally evaluated and compared with that of a non-coated CPB circuit by quantitative proteomics, using isobaric tags for relative and absolute quantification labeling tandem mass spectrometry. Plasma samples were taken three times (5 min after initiation of CPB, just before declamping and just before termination of CPB) in 12 pigs undergoing 120 min of CPB with the SEC-coated CPB circuit or a non-coated CPB circuit (n = 6, respectively). Results: Identified were 224 proteins having high protein confidence (>99%) and false discovery rate (FDR) <5%. Among these proteins, there were 25 significantly upregulated proteins in the non-coated CPB group compared to those in the SEC-coated CPB group. Dominant protein functions were platelet degranulation, serine-type (cysteine-type) endopeptidase inhibitor activity and serine-type endopeptidase activity in the 25 proteins. Bioinformatics analysis similarly revealed upregulation of proteins belonging to platelet degranulation and negative regulation of endopeptidase activity in the non-coated CPB group; these upregulations were effectively attenuated in the SEC-coated CPB group. Conclusion: The new polymer (SEC)-coated CPB circuit effectively attenuated upregulation of proteins compared to the non-coated CPB circuit. These proteins were associated with both proteases/protease inhibitors and platelet degranulation.